Gerenciador de ocorrência policial - GdOP: a importancia da tecnologia na área da segurança pública - PIMENTEL, Fabio Roger da Silva (2019)
This paper presents a police occurrence management tool aimed at improving and standardizing the collection, storage and retrieval of information. The objective is to provide the use of this technological resource, together with the practices of actions to combat crime in the municipality of Castanhal - Pará, not only focused on the number of registered occurrences, but also focusing on the other factors involved in this process such as motivation, crime and the victim, the time and place of the offenses, as well as, in cases of robbery, robbery (theft followed by death) or theft, a more accurate survey of the daily assets of criminals in said municipality . It also aims to reduce the difficulties faced by military police officers who carry out their duties in the city of Castanhal, since the NIOP does not have a specific system for collecting and managing the daily occurrences, and also to prevent many of these occurrences from being lost because of (Computer Aided Dispatch), due to the difficulty of inserting data in this system, currently used by NIOP / Castanhal, as it does not have a friendly and functional interface. In general, this work aims at the unification of criminal information in the PMPA, since it does not have its own unified system, which is specific to recording and consulting operational occurrences, that collects in a standardized way all the data that the many Units of the Institution produce daily throughout the state of Para. In this way, the GdOP system seeks to improve statistical work within the Military Police, standardizing the collection, storage and access service to this range of information, essential to subsidize, the high command of the Military Police (PM), and other public security, decision-making on policing plans and policies to control high crime rates in the city of Castanhal and throughout the state of Pará.